KEEFEKTIFAN LAYANAN EDUKASI TENTANG UBUDIYAH SHALAT DALAM MININGKATKAN SPIRITUALITAS PADA LANJUT USIA (LANSIA) DI DESA PAKUNIRAN PROBOLINGGO - Irfan Adi Ansyah (Najah: Journal of Research and Community Service, 2023)
The increase in the growth of the elderly in quantity has not been followed by an increase in the quality of life. Decreased productivity causes poor social, economic conditions, health status and independence. Successful aging or growing spirituality in the development of the ubudiyah of an elderly person, with this research it is possible, changes and giving understanding to the elderly object will run smoothly and grow the benefits the good one.